Financial Stress and Job Performance of Employees of a Government Agency in Negros Occidental - Meralie Mae B. Gualdrapa; Anabelle S. Palic (Philippine Social Science Journal, 2020)
Financial stress is a condition that is becoming more predominant in society nowadays, especially among employees. There are more financial challenges among employees today, and these challenges are being reflected in the workplace's daily operations.  Employees tend to bring financial problems into the workplace that affects their performance. The impact of financial stress has not been given considerable attention by human resource professionals in the government agencies in the Philippines.  Thus, the paper determines the level of financial stress and job performance of employees of a Government Agency in Negros Occidental when grouped according to age, sex, family status, position level, estimated loan obligation, and district office. Also, it determines the relationship between financial stress and job performance.